2012
DOI: 10.1177/1545968312461719
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery Following Stroke

Abstract: Background and Purpose-Augmenting changes in recovery is core to the rehabilitation process following a stroke. Hence, it is essential that outcome measures are able to detect change as it occurs; a property known as responsiveness. This paper critically reviewed the responsiveness of functional outcome measures following stroke, specifically examining tools that captured upper extremity functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 89 publications
0
21
0
1
Order By: Relevance
“…In the few cases where measurement error has been reported, its magnitude was again dependent on the assessment metric and platform, with overall mostly similar ranges (e.g., SRD of 13.2% to 95.0%) to the VPIT metrics [ 63 , 76 80 ]. Compared to conventional assessments (e.g., FMA-UE measurement error of 7.9%; ARAT of 6.1%) [ 77 , 81 ], the measurement errors of most technology-aided assessment metrics seem consistently elevated, even though comparisons are also challenged by the use of different SRD implementations. Nevertheless, we argue that this results from technology-aided assessments providing a multi-dimensional picture of the behavioral components underlying task performance, which makes them more susceptible to behavioral variability compared to the often ordinal outcome measures of conventional scales.…”
Section: Discussionmentioning
confidence: 99%
“…In the few cases where measurement error has been reported, its magnitude was again dependent on the assessment metric and platform, with overall mostly similar ranges (e.g., SRD of 13.2% to 95.0%) to the VPIT metrics [ 63 , 76 80 ]. Compared to conventional assessments (e.g., FMA-UE measurement error of 7.9%; ARAT of 6.1%) [ 77 , 81 ], the measurement errors of most technology-aided assessment metrics seem consistently elevated, even though comparisons are also challenged by the use of different SRD implementations. Nevertheless, we argue that this results from technology-aided assessments providing a multi-dimensional picture of the behavioral components underlying task performance, which makes them more susceptible to behavioral variability compared to the often ordinal outcome measures of conventional scales.…”
Section: Discussionmentioning
confidence: 99%
“…Of the n = 21 participants, 14 participants had room for improvement in the ARAT of which 64% (9/14) realized improved scores in the primary outcome measure (ARAT total ) from baseline to completion of intervention, both at immediate completion and/or 1-month post-completion (Table 1 ). 43% (6/14) had changes in the ARAT that are considered to meet significant ARAT specific thresholds [four of these participants had MDC ≥ 3 (MDC 90 = 3.0; Simpson and Eng, 2013 ) and two of these participants had MCID ≥ 5.7 both at immediate completion and/or 1-month post-completion]. The seven participants who had no room for improvement, or had a max score of 57 at ARAT, stayed at the same max level in ARAT both at immediate completion and 1-month post-completion.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in primary outcome scores (ARAT) during treatments suggested that this BCI design may deliver moderate objective positive UE motor changes, as seen in the 64% (9/14) of participant (out of those who had room for improvement) “Responders” who completed the BCI treatments protocol as designed. 43% (6/14) had changes in the ARAT who are considered to meet significant ARAT-specific thresholds [four of these participants had MDC of at least 3 (MDC 90 = 3.0; Simpson and Eng, 2013 ) and two of these participants had MCID of at least 5.7 both at immediate completion and/or 1-month post-completion]. Additionally, the largest positive changes compared to baseline in ARAT were observed 1-month post treatment for a few participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Согласно прогностическим данным Всемирной организации здравоохранения, количество инсультов в Европе неуклонно увеличивается и к 2025 г. может достигнуть более чем 1 500 000 случаев в год [1]. При этом, по данным некоторых авторов [2,3], успешное восстановление двигательной функции руки происходит лишь в 20% случаев. У пациентов, перенесших нарушение мозгового кровообращения, в первую очередь происходит изменение таких функций паретичной руки, как способность дотянуться до какого-либо объекта и производить манипуляции c ним, а также нарушение взаимодействия обеих рук.…”
unclassified